2009
DOI: 10.1248/bpb.32.1057
|View full text |Cite
|
Sign up to set email alerts
|

Effects of KP-496, a Novel Dual Antagonist for Cysteinyl Leukotriene Receptor 1 and Thromboxane A2 Receptor, on Sephadex-Induced Airway Inflammation in Rats

Abstract: Bronchial asthma is characterized by chronic airway inflammation. Eosinophils are involved in airway inflammation and play crucial roles in asthma. There is accumulating evidence to suggest contributions of cysteinyl leukotrienes (cysLTs) and thromboxane (TX) A(2) to the recruitment of eosinophils into lung in asthmatics. KP-496 is a novel dual antagonist for CysLT receptor type 1 and TXA(2) receptors. The aim of this study was to evaluate the anti-inflammatory effects of KP-496 on Sephadex-induced airway infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…More recently, compounds with dual antagonist properties have been designed. For example, (2-(N-(4-(4-chlorobenzenesulfonylamino)butyl)-N-(3-(4-isopropylthiazol-2-yl)methoxy)benzyl)sulfamoyl)benzoic acid (KP-496) (Mizutani et al, 2008;Ishimura et al, 2009) and YM-158 (Fig. 11) (Arakida et al, 1998) are dual TP/cysteinyl leukotriene antagonists.…”
mentioning
confidence: 99%
“…More recently, compounds with dual antagonist properties have been designed. For example, (2-(N-(4-(4-chlorobenzenesulfonylamino)butyl)-N-(3-(4-isopropylthiazol-2-yl)methoxy)benzyl)sulfamoyl)benzoic acid (KP-496) (Mizutani et al, 2008;Ishimura et al, 2009) and YM-158 (Fig. 11) (Arakida et al, 1998) are dual TP/cysteinyl leukotriene antagonists.…”
mentioning
confidence: 99%
“…The relationship between respiratory function and increase in inflammatory cells in BALF is thus still controversial. It was not clear why only 0.01% KP-496 increased inflammatory cells in BALF, but we think this result might not be a risk in clinical studies for the following reasons: (1) as shown in this study, the increase in inflammatory cells in BALF did not correlate with changes in respiratory function or histopathology, and (2) intratracheally administered KP-496 significantly inhibited Sephadex-induced airway hypereosinophilia [35] , which is known to be associated with AHR [36] .…”
Section: Discussionmentioning
confidence: 56%
“…We therefore selected the doses of ketotifen, pranlukast, and prednisolone at which they can fully perform their mechanisms of action, histamine antagonism, LTC 4 /D 4 /E 4 antagonism, and anti-inflammatory effects, respectively. From our background data and other previous reports, the doses were all 30 mg/kg [ 9 , 11 , 14 , 15 , 24 ]. The suppressive effects of the four articles included in this study are summarized in Table 1…”
Section: Discussionmentioning
confidence: 91%